2007
DOI: 10.1042/bj20070176
|View full text |Cite
|
Sign up to set email alerts
|

The mammalian oxysterol-binding protein-related proteins (ORPs) bind 25-hydroxycholesterol in an evolutionarily conserved pocket

Abstract: OSBP (oxysterol-binding protein) homologues, ORPs (OSBP-related proteins), constitute a 12-member family in mammals. We employed an in vitro [3H]25OH (25-hydroxycholesterol)-binding assay with purified recombinant proteins as well as live cell photo-cross-linking with [3H]photo-25OH and [3H]photoCH (photo-cholesterol), to investigate sterol binding by the mammalian ORPs. ORP1 and ORP2 [a short ORP consisting of an ORD (OSBP-related ligand-binding domain) only] were in vitro shown to bind 25OH. GST (glutathione… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
135
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(139 citation statements)
references
References 35 publications
4
135
0
Order By: Relevance
“…The sterol-binding domain of ORP9 is homologous to OSBP and other ORPs yet was reported not to bind photoderivatives of 25-hydroxycholesterol and cholesterol (Suchanek et al, 2007). As well, it is unclear if ORP9L or OSBP can transfer sterols from donor to acceptor membranes.…”
Section: Orp9l Is a Pi-4p-dependent Cholesterol Transfer Proteinmentioning
confidence: 99%
See 2 more Smart Citations
“…The sterol-binding domain of ORP9 is homologous to OSBP and other ORPs yet was reported not to bind photoderivatives of 25-hydroxycholesterol and cholesterol (Suchanek et al, 2007). As well, it is unclear if ORP9L or OSBP can transfer sterols from donor to acceptor membranes.…”
Section: Orp9l Is a Pi-4p-dependent Cholesterol Transfer Proteinmentioning
confidence: 99%
“…Binding of OSBP and ORP9L to phosphatidylcholine (PC) liposomes containing increasing PI-4P was determined by sedimentation ( Figure 1D). By this method, Ïł50% of ORP9L was associated with liposomes containing 10 mol% PI-4P, compared with 80 -90% for OSBP.The sterol-binding domain of ORP9 is homologous to OSBP and other ORPs yet was reported not to bind photoderivatives of 25-hydroxycholesterol and cholesterol (Suchanek et al, 2007). As well, it is unclear if ORP9L or OSBP can transfer sterols from donor to acceptor membranes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We recently reported that ORP2 binds 25OHC with micromolar affinity (31). We now wanted to study the oxysterol binding properties of ORP2 more extensively.…”
Section: Orp2 Binds Several Oxysterols With Different Affinitiesmentioning
confidence: 99%
“…The gene product of Ss18l1 (Chr 2) is a transcriptional activator that is required for calcium-dependent dendritic growth and branching in cortical neurons. Psma7 (Chr 2) encodes a member of the peptidase T1A family that functions as a 20S core alpha proteasome subunit and participates in cytoplasmic protein degradation and recycling, while OsBpl2 encodes a member of the oxysterol-binding protein family of intracellular lipid receptors, known as oxysterol binding protein-like 2 [139]. Two of the high-priority candidate genes on chromosome 17, Park2 and Pacrg, share a bidirectional promoter and are co-regulated in various tissues.…”
Section: Discussionmentioning
confidence: 99%